Trans-septal suture retraction for endoscopic orbital surgery. (2nd September 2020) - Kim, Matthew; Gudis, David A.; Tooley, Andrea A.; Kazim, Michael
ABSTRACT: Purpose: We describe a novel technique for endonasal endoscopic orbital surgery. Previously described strategies for minimally invasive orbital surgery include mobilization of the medial rectus muscle and cryosurgical retraction of the pathologic lesion. Herein we describe endoscopic trans-septal suture retraction of an orbital cavernous hemangioma to facilitate intra-orbital dissection from an external approach. Methods: A 36-year-old male presented with blurred vision in his left eye for several years, along with several months of progressive left proptosis and decreasing visual acuity. Imaging revealed a 2.5 cm orbital mass consistent with a cavernous hemangioma. The patient underwent a combined transconjunctival and endoscopic approach for resection. Results: Following left medial orbital wall and floor decompression, endoscopic trans-septal suture retraction facilitated dissection of the lesion from intraorbital structures. A complete extracapsular resection of the lesion was achieved. The inferomedial orbit was reconstructed with a synthetic implant. Conclusion: Trans-septal suture retraction is an effective adjunctive technique for endonasal endoscopic orbital tumor surgery. This technique facilitates safe retraction and dissection of soft tissue lesions from critical intraorbital structures.